KÜTAHYA SEYİTÖMER TERMİK SANTRALİ ATIK UÇUCU KÜLÜNDEN ISI YALITIM ÖZELLİKLİ GEOPOLİMER MALZEME ÜRETİMİ - Uğur KUT; İskender IŞIK (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi, 2021)
In order to be used in buildings, it is aimed to produce a geopolymer material with high void rate, low density and low moisture content, high performance in terms of thermal insulation, environmentally friendly, which does not need to consume large amounts of energy and inexpensive. Therefore, heat insulated geopolymer building material was produced by using Industrial waste base material called coal fly ash of Seyitömer Thermal Power Plant (UK) and, potassium hydroxide (KOH) and sodium silicate as activator, metallic aluminum as foam forming agent and fumed silica (FS). The thermal conductivity coefficient of our D10 coded sample in terms of thermal insulation is 0.085 W / m oK. The results of the study were determined as pore volume value 0.45 cm3, pore size distribution (average) 3.80 nm, specific surface area 25.80 m2/ g, total porosity (Archimedes) 77.00%, water vapor permeability 3.00 μ, and TS EN ISO 11925-2 small flame test (SFI) “ Bclass ”. As a result, it has been determined in terms of economy and technological features the use of waste fly ash (UK) of Kütahya Seyit Ömer thermal power plant in the production of geopolymer materials for thermal insulation in buildings.